Ideologies in Advertisements of ‘Fair & Lovely’ and ‘Glow & Lovely’ by Unilever Pakistan: A Comparative Multimodal Critical Discourse Analysis - Bibi, Hafsa; Raza, Hassan; Qasim, Hafiz Muhammad (Pakistan Languages and Humanities Review, 2025)
The study examines the ideological shifts in two advertisements for Unilever Pakistan's beauty creams, ‘Fair & Lovely’ and ‘Glow & Lovely’. It analyses how concepts of fairness and beauty are constructed to show colourism and gender bias in advertising. Employing the qualitative approach, the study analyses two advertisements, applying Fairclough’s three-dimensional model for Critical Discourse Analysis and Machin and Mayr’s Multimodal Critical Discourse Analysis framework. The results show that the first advertisement reinforces racist and antifeminist ideologies by promoting fairness as the ideal standard of beauty. In contrast, the second advertisement challenges these norms by portraying diverse skin tones and emphasising an inclusive ideology. This shift in messaging highlights the broader societal criticism faced by the company. The study concludes that the rebranding reflects a shift towards ideologies that challenge traditional beauty norms. Companies should align advertising strategies with inclusive values and avoid beauty standards that marginalise identity and diversity.